2011
DOI: 10.1158/0008-5472.can-11-2015
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Permeable NM23 Blocks the Maintenance and Progression of Established Pulmonary Metastasis

Abstract: Occult metastases are a major cause of cancer mortality, even among patients undergoing curative resection. Therefore, practical strategies to target the growth and persistence of already established metastases would provide an important advance in cancer treatment. Here, we assessed the potential of protein therapy using a cell permeable NM23-H1 metastasis suppressor protein. Hydrophobic transduction domains developed from a screen of 1,500 signaling peptide sequences enhanced the uptake of the NM23 protein b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
(40 reference statements)
2
27
0
Order By: Relevance
“…NME1 also reduces metastasis of colon cancer cells to the liver, potentially by regulating myosin light chain phosphorylation (56). A recent study indicates that a newly developed cell-permeable form of NME1 probably blocks pulmonary metastasis of several cancer cell lines (57). All of the experiments of Lim et al (57), conducted with NME1, reveal that the short form of the protein has moderate but efficient antimetastatic activity, a finding confirmed in our model of metastasis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…NME1 also reduces metastasis of colon cancer cells to the liver, potentially by regulating myosin light chain phosphorylation (56). A recent study indicates that a newly developed cell-permeable form of NME1 probably blocks pulmonary metastasis of several cancer cell lines (57). All of the experiments of Lim et al (57), conducted with NME1, reveal that the short form of the protein has moderate but efficient antimetastatic activity, a finding confirmed in our model of metastasis.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study indicates that a newly developed cell-permeable form of NME1 probably blocks pulmonary metastasis of several cancer cell lines (57). All of the experiments of Lim et al (57), conducted with NME1, reveal that the short form of the protein has moderate but efficient antimetastatic activity, a finding confirmed in our model of metastasis. However, we observed that NME1L dramatically inhibited pulmonary metastasis of cancer cells.…”
Section: Discussionsupporting
confidence: 78%
“…MTD13, MTD57, and MTD108 were derived from signal sequences from NP_639877, CAD0547.1, NP_629842.1, and NP_003842, respectively, as previously described (26, 27). Histidine-tagged fusion proteins containing EGFP or the full-length 46-kDa RUNX3 protein (33) and MTD13, MTD57, MTD85, MTD108, the FGF4 MTS (M m , AAVLLPVL-LAAP), or a random sequence (S, SANVEPLERL) were cloned into pET-28a(+) (Novagen) and expressed in Escherichia coli BL21-CodonPlus (DE3) cells.…”
Section: Methodsmentioning
confidence: 99%
“…MITT was used previously to deliver peptides and proteins to a variety of tissues (notably liver, lung, pancreas, and lymphoid tissues), resulting in dramatic protection against lethal inflammatory diseases (2125), suppression of pulmonary metastases (26), and inhibition of subcutaneous tumor xenografts (27). The technology exploits the ability of hydrophobic macromolecule transduction domains (MTD) to promote bidirectional transfer of peptides and proteins across the plasma membrane (2729).…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds have been reported to elevate tumor cell Nme1 expression as well (Jiang et al 1988;Lin et al 2002;Liu et al 2000;Natarajan et al 2002) and thus are additional candidates at least for preclinical testing. A cell permeable Nme1 construct suppressed development of pulmonary metastases in mice and diminished already established metastases, with a prolongation of overall survival (Lim et al 2011). A peptide that disrupts the interaction of Nme1 and h-Prune has been identified, and preclinical studies were performed in breast and prostate cancers as well as neuroblastoma (Carotenuto et al 2014;Carotenuto et al 2013;D'Angelo et al 2004 Another translational approach is based on the identification of genes which expression patterns were inversely related to that of Nme1 protein.…”
Section: Translational Advances In Cancer Therapy Based On Targeting mentioning
confidence: 99%